Integrasi Nilai-nilai Moral dan Spiritual dalam Pembelajaran Pendidikan Agama Islam - Munawir Munawir; Nurul Hidayah; Siaka Dewi Nawangsari (FKIP, Universitas Palangka Raya, 2026)
This study aims to identify the role of education, especially in Islamic Primary Schools (Madrasah Ibtidaiyah/MI), in improving academic quality and supporting students’ moral development. In addition, the research discusses the principles of life and human nature that influence students’ morality and character formation. The study examines the significance of education that integrates moral, ethical, and spiritual values, especially in MI, as an important foundation for shaping strong personalities and responsible behavior in adulthood. The methodology employed involves the analysis of various sources, including literature reviews, books, and relevant scientific references, to understand the concept of Islamic education that aligns academic achievement with moral and spiritual development. The findings highlight the importance of the relationship between human nature and the cultivation of Islamic values among students in schools. These values need to be integrated into learning activities through appropriate teaching methods that correspond to the characteristics of the values being developed. The results indicate that Islamic education contributes to building students’ awareness, discipline, responsibility, and noble conduct. In conclusion, Islamic religious education should focus on forming strong character and morality by integrating Islamic values into practical, contextual, and relevant learning that meets the demands of the time in modern society.